2011
DOI: 10.1590/s0100-879x2011007500092
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of catecholaminergic medullary pathways in cardiovascular responses to acute changes in circulating volume

Abstract: Water deprivation and hypernatremia are major challenges for water and sodium homeostasis. Cellular integrity requires maintenance of water and sodium concentration within narrow limits. This regulation is obtained through engagement of multiple mechanisms and neural pathways that regulate the volume and composition of the extracellular fluid. The purpose of this short review is to summarize the literature on central neural mechanisms underlying cardiovascular, hormonal and autonomic responses to circulating v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Previous studies have indicated that A2 neurons are involved in the regulation of body fluid homeostasis [10][14], [22][25]. However, there was previously no evidence to support the contribution of these neurons to the autonomic control of the circulating volume composition.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have indicated that A2 neurons are involved in the regulation of body fluid homeostasis [10][14], [22][25]. However, there was previously no evidence to support the contribution of these neurons to the autonomic control of the circulating volume composition.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown the importance of medullary noradrenergic neurons in the integration of the mechanisms involved in the autonomic, cardiovascular and respiratory systems [3], [10][15], [22], [24], [25], [27], [33][36]. With regard to the A1 noradrenergic cluster, several authors have shown that these neurons are important for the response induced by changes in the circulating volume [3], [12], [15], [22], [27], [33][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1980s, important study revealed that HSI was able to quickly restore blood pressure and cardiac output [ 5 ]. Although these hemodynamic responses to HSI in animals with hemorrhagic shock are already well established in the literature [ 6 9 ], there is still dearth of information about the involvement of central nervous system (CNS) in HSI induced resuscitation.…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that OT induced a concentration-dependent relaxation in renal arteries both in vivo and in vitro. The complex mechanisms involved in the genesis and maintenance of the renal vasodilation induced by increases plasma sodium concentration are poorly understood and seem to involve hormonal and autonomic mechanisms [8] , [10] , [14] , [41] , [42] . Our in vitro results show that OT can act on oxytocin receptors in the renal vasculature to promote vasodilatation.…”
Section: Discussionmentioning
confidence: 99%